Analisis Aktor dan Relasi Antar Aktor Pemerintah Daerah dan DPRD dalam Pembuatan APBD Kota Makassar - Hadi Yudho Prio Wibowo; Muhammad Gaus; Nurhaerani Tenriwaru; Umi Umairah Suharadi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This thesis research aim to analyze the actors and relationship between regional government and DPRD actors in making APBD. Through the analysis of actors the relationship between actors, this research provide a “general idea” to the public, academics, government and DPR, regional government and provincial, district and city DPRDs about the phenomena and facts behind the making of APBD.This research is qualitative study, which produces descriptive data in the form of written or spoken words from and about regional government and DPRD actors in making APBD – either as individuals, groups or as institutions – and their observable behavior.The results of the research on the analysis actors and relationship between actors show that the actors of the Regional Government and DPRD of Makassar City in making APBD are pathologies of actors who tend to prioritize the interests of themselves and their groups rather than the interests of the community. The spectrum of social facts such as conflicts of interest, group dynamic, network, and the authority of regional government and DPRD actors is very dominant in making APBD.APBD of Makassar City for the 2020 Fiscal Year which is established though the Makassar City Regional Regulation Number 09 of 2020 dated December 30, 2019: “responds more to the wishes (will) of the Regional Government and DPRD of Makassar City rather than responding to the needs of the people of Makassar City”